Epidemiology, diagnostics, and biomarkers of autoimmune neuromuscular junction disorders. Issue 2 (February 2022) - Punga, Anna Rostedt; Maddison, Paul; Heckmann, Jeannine M; Guptill, Jeffrey T; Evoli, Amelia
Summary: Autoimmune neuromuscular junction disorders are rare. However, myasthenia gravis is being increasingly recognised in people older than 50 years. In the past 5–10 years, epidemiological studies worldwide suggest an incidence of acetylcholine receptor antibody-positive myasthenia gravis of up to 29 cases per 1 million people per year. Muscle-specific tyrosine kinase antibody-positive myasthenia gravis and Lambert-Eaton myasthenic syndrome are about 20 times less common. Several diagnostic methods are available for autoimmune neuromuscular junction disorders, including serological antibody, electrophysiological, imaging, and pharmacological tests. The course of disease can be followed up with internationally accepted clinical scores or patient-reported outcome measures. For prognostic purposes, determining whether the disease is paraneoplastic is of great importance, as myasthenia gravis can be associated with thymoma and Lambert-Eaton myasthenic syndrome with small-cell lung cancer. However, despite well defined diagnostic parameters to classify patients into subgroups, objective biomarkers for use in the clinic or in clinical trials to predict the course of myasthenia gravis and Lambert-Eaton myasthenic syndrome are needed.